2020
DOI: 10.5194/esd-2020-37
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A New View of Heat Wave Dynamics and Predictability over the Eastern Mediterranean

Abstract: Abstract. Skillful forecasts of extreme weather events have a major socio-economic relevance. Here, we compare two complementary approaches to diagnose the predictability of extreme weather: recent developments in dynamical systems theory and numerical ensemble weather forecasts. The former allows us to define atmospheric configurations in terms of their persistence and local dimension, which inform on how the atmosphere evolves to and from a given state of interest. These metrics may be used as proxie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Several definitions, metrics, and indices have been proposed in the literature and are used by the meteorological services and other authorities. Some of these definitions are based on local criteria and absolute thresholds of temperature, while others are calculated on percentage-based standards or they also include additional variables such as relative humidity or planetary boundary layer height 5,6,57 . Following Russo et al 58 , we defined a heatwave as a period of at least three consecutive days with a maximum temperature above a daily percentage-based threshold.…”
Section: Heatwave Definition and Calculationsmentioning
confidence: 99%
“…Several definitions, metrics, and indices have been proposed in the literature and are used by the meteorological services and other authorities. Some of these definitions are based on local criteria and absolute thresholds of temperature, while others are calculated on percentage-based standards or they also include additional variables such as relative humidity or planetary boundary layer height 5,6,57 . Following Russo et al 58 , we defined a heatwave as a period of at least three consecutive days with a maximum temperature above a daily percentage-based threshold.…”
Section: Heatwave Definition and Calculationsmentioning
confidence: 99%
“…These studies have focused on individual time‐slices of the atmosphere. Yet, recent studies have demonstrated the potential of using the temporal evolution of the metrics to study the predictability of extreme weather events (Hochman, Scher, et al., 2020; Hochman et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Complementary model experiments will be able to confirm the critical role any mechanism may play, separately and together with the other co‐occurring mechanisms, in the aforementioned anomalous conditions. The current study may aid in the formulation of dynamic predictors of warm and dry persistent events over the EM, which are becoming more and more relevant due to global warming and the proximity to arid climate regions (Hochman et al ., 2021a; 2021b). In particular, our results indicate the relevance of Mediterranean cyclones to warm extremes on their downstream side, which means that a cyclone's impact is non‐local in both space and time.…”
Section: Discussionmentioning
confidence: 99%